PRODUKTIVITAS DAN RENDEMEN CUKA KAYU DAN ARANG MANGIUM (Acacia mangium) DI KELOMPOK TANI HUTAN ALIMPUNG DESA TIWINGAN LAMA - Setiani Rahma Pratiwi; Lusyiani Lusyiani; Trisnu Satriadi (Jurnal Sylva Scienteae, 2020)
This study aimed to analyze the productivity and yield of Mangium Wood Vinegar and Charcoal in the Forest Farmer Group Alimpung in Tiwingan Lama Village. The method used to determine productivity is to calculate the amount of raw materials and total time. The yield is measured by counting the amount of raw material and wood vinegar or charcoal produced.  The results showed that the average productivity of acacia wood vinegar was 0.037 kg / hour and acacia wood charcoal was 0.230 kg / hour. The processing process produces a yield 7.500% wood vinegar and 46.089% wood charcoal. The productivity of processing mangium wood into wood vinegar and charcoal is 0.267 kg / hour and the yield is 53.589%. Waste generated from the manufacture of wood vinegar and charcoal amounted to 46.411%. Productivity and yield are influenced by tools, raw materials and workers. Keywords: Productivity; yield; wood vinegar; charcoal; mangium